Detecting stochastic inclusions in electrical impedance tomography. (26th October 2017) - Barth, Andrea; Harrach, Bastian; Hyvönen, Nuutti; Mustonen, Lauri
Abstract: This work considers the inclusion detection problem of electrical impedance tomography with stochastic conductivities. It is shown that a conductivity anomaly with a random conductivity can be identified by applying the factorization method or the monotonicity method to the mean value of the corresponding Neumann-to-Dirichlet map provided that the anomaly has high enough contrast in the sense of expectation. The theoretical results are complemented by numerical examples in two spatial dimensions.